2011
DOI: 10.1016/j.jmb.2011.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Drugs: The Interaction of Antitumor Compound MKT-077 with Human Hsp70 Chaperones

Abstract: The Hsp70 chaperones (Heat shock protein 70 kDa) are key to cellular protein homeostatis. However, they also have the ability to inhibit tumor apoptosis, and contribute to aberrant accumulation of hyperphosphorylated tau in neuronal cells affected by tauopathies, including Alzheimer’s disease. Hence, Hsp70 are increasingly been identified as targets for therapeutic intervention in these widely abundant diseases. Hsp70 proteins are allosteric machines and offer besides classical active site targets, also opport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
215
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 172 publications
(226 citation statements)
references
References 82 publications
11
215
0
Order By: Relevance
“…The results showed that YM-08 (30 μM) decreased the levels of pS396/404 and total tau by ∼40% and ∼60%, respectively ( Figure 4C). This cellular activity is not as dramatic as that of MKT-077, which reduced tau levels by >80% at 30 μM ( Figure 4D); 23 however, reducing tau by only ∼50% is predicted to provide benefits in some AD models. 4 Importantly, we also confirmed that, like MKT-077 and other Hsp70 inhibitors, 12,41,42 YM-08 did not induce a stress response, based on the unchanged levels of stress inducible Hsp72 (HSPA1) in the treated cell lysates ( Figure 4C).…”
Section: ■ Results and Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…The results showed that YM-08 (30 μM) decreased the levels of pS396/404 and total tau by ∼40% and ∼60%, respectively ( Figure 4C). This cellular activity is not as dramatic as that of MKT-077, which reduced tau levels by >80% at 30 μM ( Figure 4D); 23 however, reducing tau by only ∼50% is predicted to provide benefits in some AD models. 4 Importantly, we also confirmed that, like MKT-077 and other Hsp70 inhibitors, 12,41,42 YM-08 did not induce a stress response, based on the unchanged levels of stress inducible Hsp72 (HSPA1) in the treated cell lysates ( Figure 4C).…”
Section: ■ Results and Discussionmentioning
confidence: 85%
“…This pocket is framed by a number of residues, including S208, S221, T222, D225, H227, and L228 ( Figure 3C) that are known to be sensitive to addition of MKT-077. 23 When the side chains of these residues were allowed to freely rotate, they adjusted to define the YM08-binding pocket (see Figure 3A). In this orientation, the benzothiazole of YM-08 was predicted to access a deep cleft composed of hydrophobic and cationic residues (T12, K70, R71, R75, V81, Y148, T203, G223, and T225).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the reasons for this slower development of Hsp70 inhibitors has been that there are 10 isoforms in mammalian cells and selective inhibitors are currently not available (9)(10)(11)(12)(13). Moreover, Hsp70 proteins are very promiscuous, affecting many proteins in the cell, while Hsp90 proteins are slightly more discriminating in regard to their clientele.…”
Section: Introductionmentioning
confidence: 99%